Hierarchical effects of advertising - Chandukala, Sandeep R. (Henry Stewart Talks, 2010)
Multistage processes, Understanding intermediate effects of advertising, A simple Bayesian approach for capturing intermediate effects with heterogeneous response segments, Application based on cross-sectional brand tracking data to demonstrate the proposed modeling strategy and model comparisons